Nabokov, Rushdie, and the Transnational Imagination - Trousdale, R. author. aut Link
X, 241 p.
Keywords: Using Vladimir Nabokov and Salman Rushdie's work, this study argues that transnational fiction refuses the simple oppositions of postcolonial theory and suggests the possibility of an inclusive global literature.